Mini-symposium - On Multi-stories History - Part 1
Audio recording of a mini-symposium presented by Central European University, entitled "On Multi-stories History" held in István Rév's honor on March 12, 2001. The moderator is the President and Rector of the CEU, Yehuda Elkana. The lectures are delivered by Natalie Zemon Davis from the University of Toronto and Carlo Ginzburg from the University of California, Los Angeles. The lectures are followed by a panel discussion entitled "Socio-political Implications of Writing and Thinking in Terms of Multi-stories History" where Prof. István Rév (Director of OSA Archivum and member of the CEU Board of Trustees) gives a presentation about multiple stories and their social consequences. The first part of István Rév’s presentation is recorded here.